Extraction and evaluation of crude pili pulp oil - Comia, Wilma L.; Del Valle, Mercedita (1979.)
The study was primarily aimed to extract and evaluate crude oil from pilipulp. It was divided into two phases. Phase I involved the determination of the best extraction method. Mechanical pressing and solvent extraction method. Mechanical pressing and solvent extraction methods were compared based on percent yield, quality of oil extracted and convenience to the researcher. Mechanical pressing gave a lower % yield but a better product in terms of color, odor and clarity. Phase II-A sought to determine whether deterioration of the oil takes place by hydrolysis and/or oxidation during post-harvest storage of pilifruits. The % free fatty acid content, which was used to measure the extent of hydrolysis, showed an increasing trend as post-harvest storage was prolonged. Values however, remained small reaching only 6.13% at seven days storage. Peroxide values did not show a definite trend with storage time but levels were relatively high even at three days storage and reached an average value of 22.44 after seven days. In Phase II-B some physical and chemical constants were determined. The iodine value was found to be 80.12 indicating that crude pilipul oil is characterized by low unsaturation. The saponification value, 174.28, indicates that the oil contains longer chain fatty acids on the average than most common fats. The melting point of crude pilipulp oil ranges from 5-7°C or 41-44°F. Viscosity, relative to water, at 15.5°C was found to be approximately 636.7 millipoise with a specific gravity of 0.920.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Pilipulp oil